Russia’s Foreign Policy in Central and East Asia: New Perspectives, Problems and Challenges - A. G. Kuznetsov (Евразийская интеграция: экономика, право, политика, 2019)
The article refers to the review and analysis of Russia’s relations with Central and East Asian countries, special attention is paid to understanding the prospects of future cooperation, especially in economic and military-strategic areas. Thus, the Russian economic cooperation in the oil and energy trade with the countries of East Asia and the Far Eurasian economic integration with the countries of Central Asia form a positive economic «climate» between the regions, as well as provide stability and prospects of cooperation. However cooperation and interaction generates not only incentives for the development, but also evoke some problems and challenges, which will be mentioned in this article.